2021
DOI: 10.1186/s13063-021-05795-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementation with vitamins A, B, C, D, and E on disease severity and inflammatory responses in patients with COVID-19: a randomized clinical trial

Abstract: Background and objective Because of the effect of vitamins on modulating the immune system function, we have evaluated the effect of supplementation with vitamins A, B, C, D, and E in ICU-admitted patients with COVID-19. Methods This study was a randomized and single-blinded clinical trial in which 60 subjects were randomly assigned to two groups. The intervention group (n=30) received vitamins, and the control group did not receive any vitamin or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 30 publications
2
70
1
1
Order By: Relevance
“…The latter could be addressed by performing a meta-analysis. Baseline severity is presented as Sequential Organ Failure Assessment Score (SOFA) (23,28) as Acute Physiology And Chronic Health Evaluation (APACHE II) (29) or other (25,32). *Data from the entire cohort of patients (not only critically ill) are presented.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter could be addressed by performing a meta-analysis. Baseline severity is presented as Sequential Organ Failure Assessment Score (SOFA) (23,28) as Acute Physiology And Chronic Health Evaluation (APACHE II) (29) or other (25,32). *Data from the entire cohort of patients (not only critically ill) are presented.…”
Section: Discussionmentioning
confidence: 99%
“…However, we attempted to address this limitation by performing a sensitivity analysis of the 5 randomized controlled trials. Lastly, the included studies (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in the meta-analysis did not consistently report on adverse events potentially related to administration of vitamin C, such as oxalate nephropathy, hypernatremia and glucometer error. Nevertheless, relevant evidence before the pandemic indicated that high-dose vitamin C may be relatively safe (36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations